Hubungan Kekerabatan Jamur Pelapuk Putih Pleurotus spp. dengan Analisis Isoenzim - Achmad Achmad; Elis N. Herliyana; Ficky R. Agustian (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2009)
Pleurotus spp. is anedible mushroom commonly found on stem of wide leaftrees or other wooden plants in the forest. A number ofPleurotus species are found in Indonesia, and some of themhave been cultivated. An accurate technique is needed toidentify the species of Pleurotus correctly; one of the methodis the isoenzyme technique. Apart from its simplicity, cheapnessand quickness, this method also gives accurate informationon phylogenetic relationship among the Pleurotusspp. The technique was used to determine phylogeneticrelationship in 6 isolates of Pleurotus spp., i.e., Pleurotussp.8, Pleurotus sp.6, Pleurotus sp.1, Pleurotus sp.7, andPleurotus sp.9, using the GOT System. Results of the analysisindicated that all the Pleurotus isolates tested produced twobands with similar thickness, except for Pleurotus sp.1 thatproduced one band that move to the cathode (-). Anotherisolate of Pleurotus spp. produced bands tend to move to theanode (+). The genetic distances between Pleurotus sp.8was similar to that of Pleurotus sp.9, while that of Pleurotussp.6 was similar to Pleurotus sp.7. Genetic distances ofPleurotus sp.8 or Pleurotus sp.9 was similar to Pleurotus sp.6or Pleurotus sp.7, with the longest distance on Pleurotussp.1. Pleurotus sp.1 showed a different migration distance,where one of the isoenzym band tend to move to thecathode (-). This indicated that Pleurotus sp.1 has differentphylogenetic relationship with the other Pleurotus spp.